Genes and gene models, an important distinction. Issue 1 (4th August 2019) - Schnable, James C.
Summary: Genome sequencing has fundamentally changed how plant biologists think about genes. All or nearly all genes can ultimately be associated with a gene model. However, many gene models appear to play little or no role in the traits of an organism. A range of structural, molecular, population and evolutionary features all show a separation between genes with known phenotypes and the overall set of annotated gene models. These different features could be combined to develop models to distinguish the genes that determine the traits of plants from the subset gene other annotated gene models which are unlikely to play a role in doing so. Efforts to identify the subset of annotated gene models likely involved in specifying the characteristics of plants would help aid a wide range of researchers. Abstract : James Schnable is an honourably mentioned finalist of the 2018 New Phytologist Tansley Medal competition for excellence in plant science. See Lennon & Dolan, in this issue of New Phytologist (2020, 228 : 5), for more details.